The Procedures in English-Indonesian Translation of Islamic Terms - Frihatmawati, Rizky; Yuskar, Bobby Octavia; Yastanti, Unpris; Nurmalia, Lia (English Education and Literature Journal (E-Jou), 2024)
When translating a message, a translator needs to identify the most equivalent natural expression in Target Language (TL). Nevertheless, it is not always feasible to discover the corresponding translation for culturally specific text. The translators frequently need various procedures to accomplish the translation tasks. This study examines the procedures used in translating Islamic terms and the most common procedures used by translators in the book "Reclaim Your Heart and its translation. The researcher employed a qualitative method for collecting descriptive data by explaining the translation procedures provided by Newmark. The data was gathered by analyzing Islamic terms in the source language (SL) and target language (TL) texts, categorizing terms according to the translation procedures used. After analyzing the data, four types of translation procedures were found in thirty-four pieces of data. They are transference, couplet, naturalization, and cultural equivalent. The most common translation procedure used in translating Islamic terms by the translator is transference. The translator maintained the English Islamic terms (SL) in Indonesian text (TL) without some linguistic changes (phonological or morphological). This approach was used for translating proper names, places, verses, the book's title, and the terms used several times in the book.